Renal Function and All-Cause Mortality Risk Among Cancer Patients. Issue 20 (May 2016) - Yang, Yan; Li, Hui-yan; Zhou, Qian; Peng, Zhen-wei; An, Xin; Li, Wei; Xiong, Li-ping; Yu, Xue-qing; Jiang, Wen-qi; Mao, Hai-ping
Abstract : Abstract: Renal dysfunction predicts all-cause mortality in general population. However, the prevalence of renal insufficiency and its relationship with mortality in cancer patients are unclear. We retrospectively studied 9465 patients with newly diagnosed cancer from January 2010 to December 2010. Renal insufficiency was defined as an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 using the Chronic Kidney Disease Epidemiology Collaboration equation. The hazard ratio (HR) of all-cause mortality associated with baseline eGFR was assessed by Cox regression. Three thousand sixty-nine patients (32.4%) exhibited eGFR <90 mL/min/1.73 m 2 and 3% had abnormal serum creatinine levels at the time of diagnosis. Over a median follow-up of 40.5 months, 2705 patients (28.6%) died. Compared with the reference group (eGFR ≥ 60 mL/min/1.73 m 2 ), an elevated all-cause mortality was observed among patients with eGFR < 60 mL/min/1.73 m 2 stratified by cancer stage in the entire cohort, the corresponding hazard ratios were 1.87 (95% CI, 1.41–2.47) and 1.28 (95% CI, 1.01–1.62) for stage I to III and stage IV, respectively. However, this relationship was not observed after multivariate adjustment. Subgroup analysis found that eGFR < 60 mL/min/1.73 m 2 independently predicted death among patients with hematologic (adjusted HR 2.93, 95% CI [1.36–6.31]) and gynecological cancer (adjusted HR 2.82, 95% CI [1.19–6.70]), but not in those with other cancer. Five hundred fifty-seven patients (6%) had proteinuria. When controlled for potential confounding factors, proteinuria was a risk factor for all-cause mortality among patients in the entire cohort, regardless of cancer stage and eGFR values. When patients were categorized by specific cancer type, the risk of all-cause death was only significant in patients with digestive system cancer (adjusted HR, 1.85 [1.48–2.32]). The prevalence of renal dysfunction was common in patients with newly diagnosed cancer. Patients with eGFR < 60 mL/min/1.73 m 2 or proteinuria were associated with increased risk for all-cause mortality, this relation depended on cancer site.